Multimodal assessment of functional and structural retinal changes in patients undergoing accelerated corneal collagen cross-linking - Gonzalez, José Estrela Rego (2017)
Trabalho de Projeto do Mestrado Integrado em Medicina apresentado à Faculdade de Medicina